Polymorphisms in the IL-6 and TNF-α gene are associated with an increased risk of abdominal aortic aneurysm. (15th April 2021) - Jabłońska, Agnieszka; Zagrapan, Branislav; Neumayer, Christoph; Eilenberg, Wolf; Scheuba, Andreas; Brostjan, Christine; Demyanets, Svitlana; Klinger, Markus; Nanobachvili, Josif; Huk, Ihor
Abstract: Background: An abdominal aortic aneurysm (AAA) is a complex disease of the aging population that is associated with inflammation and the cellular immune response. To investigate the influence of interleukin ( IL ) -6 and tumor necrosis factor ( TNF ) -α single nucleotide polymorphisms (SNPs) on the risk of AAA formation and progression, the frequency of AAA and its associated risk factors were determined. Method: Four SNPs in the IL-6 (−174G/C, rs1800795; −572G/C, rs1800796) and TNF-α (−238G/A, rs361525; −308G/A, rs1800629) genes were studied by the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) in patients with AAA and healthy volunteers. The mRNA expression and plasma IL-6 and TNF-α levels were also determined. Results: A mutation detected in at least one allele of the IL-6 -174G/C SNP was associated with a 2-fold increased risk of AAA occurrence (OR: 2.08; 95% CI: 1.15–3.76; p = 0.014, in the dominant model). An increased risk of AAA incidence among heterozygous carriers of the TNF-α − 308G/A genotype was observed (OR: 2.06; 95% CI: 1.17–3.62; p = 0.011, in the overdominant model). The wild-type genotypes of the IL-6 -174G/C and the TNF-α -308G/A SNPs coexisted more frequently in healthy subjects than in AAA patients and was associated with decreased risk of AAA ( p < 0.001). Moreover, elevated levels of IL-6 and TNF-α were associated with an increased risk of hypertension ( p < 0.001 and p = 0.022, respectively). Conclusions: The IL-6 -174G/C and the TNF-α -238G/A gene polymorphisms are associated with an increased risk of abdominal aortic aneurysm development. Highlights: The IL-6 -174G/C and the TNF-α -308G/sA SNPs are predictive factors for AAA formation. The CC genotype of the IL-6 -174G/C SNP was associated with an increased risk of CVAD. The AA genotype of the TNF-α -308G/A polymorphism had high mRNA expression. The GA and AA genotypes of the TNF-α -308G/A SNP was associated with high TNF-α level.